LANGUAGE POLICY PLANNING AS A POLITICAL TOOL FOR SOCIAL STRATIFICATION: ANALYSING THE CASE OF PARAGUAY - Pinilla- Portiño, Nykoll (PEOPLE: International Journal of Social Sciences, 2018)
English has been the medium of instruction since the beginning of the 20th century in the Philippines during the arrival of the Americans. This has been incorporated holistically in the society through the educational system, communication, mass media, publications and social media. It is given therefore that Filipino learners are bilingual– i.e., speaking both Filipino (the native tongue) and English as Second Language (ESL). After a century though, proficiency in the language is still a difficulty and an anxiety, especially from public school learners. In Taytay Senior High School (a public senior high school), Grade 11 students were observed of certain levels of difficulties in reading, writing, speaking and listening. In this study, the researchers probed deeper into the following: a.) the difficulties experienced by grade 11 students b.) the factors that led to such difficulties and c.) the articulated ways to help them overcome such difficulties in English proficiency. As a descriptive study, the researchers used pre-survey, survey, FGD and extensive literature review as methodologies. The survey results revealed problematic stages on vocabulary, training and knowledge, confidence and self-esteem and interest. Articulated in the FGD furthermore were issues of generation, practice/articulation, and system as factors that led to difficulties in reading writing, speaking and listening. On the other hand, Grade 11 students underscored power of mind, the use of native language and practice as methodical solutions to the problem. Further directions of this study could include elaboration of the FGD results that pertain to issues of generation, practice/articulation and system. The use of native language could also be expounded on future studies.